PENERAPAN ASUHAN KEPERAWATAN PASIEN DIARE DALAM GANGGUAN PEMENUHAN KEBUTUHAN ELIMINASI - Ratna Mahmud (Media Keperawatan:Politeknik Kesehatan Makassar, 2019)
ABSTRACTBackground: Diarrhea is a bowel movement in liquid form more than three times a day, and usually lasts for two days or more. In the case of diarrhea there is a change in the pattern of faecal elimination in the form of decreased absorption in the intestine. Diarrhea is a disease that can affect all age groups, especially among children less than 5 years old. Based on the 2018 Riskesdas data, the prevalence of diarrhea in infants in Indonesia has increased quite significantly. Objective: To describe nursing care in pediatric patients with diarrhea in impaired fulfillment of the need for bowel elimination patterns. Method: using descriptive method. Results: Patients with diarrhea cases obtained data from the client's mother said the client defecated as much as 5x. The client's mother said the client's stool was thin, there was pulp and brown. The client's mother said the client complained of stomach pain. The client's mother also said the client vomited 7 times. Interventions assessing the color, frequency and consistency of stool, identifying causes and intravenous therapy are very helpful in handling diarrhea elimination patterns. Conclusion: In nursing diagnoses, disorders of elimination pattern: Diarrhea is related to the infection process, observing stool characteristics, causes of diarrhea, intestinal peristaltic observation, intra collaboration veins education and drugs , antipieretik, antibiotic  and antiadiarhea have an influence in dealing with diarrhea. Suggestion: In order to obtain optimal results in the assessment and determination of diagnoses, it is better to do an interpersonal approach so that there is a trusting relationship between the patient and family and the nurse. The nurse should involve the patient and family in implementing nursing actions.